An analysis of section 86(10) of the National Credit Act no. 32 of 2005 - Mwape, Bibiana Mwansa (Department of Commercial Law, 2015)
The financial sector in general is a difficult industry to regulate, as there is a need to balance the competing interests of the various stakeholders. Tampering with the cornerstone of the capitalist system naturally arouses diverging views and is often the subject of many debates as is evidenced by the debates surrounding the National Credit Act ('NCA'). Nonetheless, its regulation can be a weapon to fight against poverty and inequality as evidenced by the purposes of the NCA. The object of this research is to analyse the law on debt review, focusing on the credit provider's right contained in s 86(10) of the NCA to terminate the debt review process.